Histamine-induced inositol phospholipid breakdown in the longitudinal smooth muscle of guinea-pig ileum. - Donaldson, J. (1985)
The characteristics of histamine-stimulated inositol phospholipid breakdown in slices of guinea-pig ileal smooth muscle and cerebellum have been investigated. In cerebellar slices the inhibition of the inositol phospholipid response to histamine by mepyramine was consistent with competitive antagonism of histamine H1-receptors. In slices of the longitudinal smooth muscle of guinea-pig ileum, mepyramine produced only a weak inhibition of the response to histamine, at concentrations up to 1 microM. This was in striking contrast to the potent competitive antagonism of the H1-mediated contractile responses obtained with mepyramine in this tissue. The H1-receptor antagonists (+)-chlorpheniramine and promethazine similarly had no effect on the EC50 value for histamine in guinea-pig ileum, while promethazine competitively antagonized the muscarinic receptor-mediated inositol phospholipid response in this tissue (Ka 3.6 X 10(7)M-1). Cimetidine, on its own, did not significantly inhibit the inositol phosphate accumulation elicited by histamine in ileum. In the presence of 0.2 microM mepyramine, cimetidine (0.1 mM) produced a small parallel shift of the histamine concentration-response curve (Ka 3 X 10(4) M-1). This inhibition, however, was not consistent with antagonism of an H2-receptor-mediated response. The effect of a range of histamine analogues on inositol phospholipid breakdown was determined. Dose-response curves were constructed and characterized in terms of the EC50, slope and maximal response attainable relative to histamine. The H1-agonists, N alpha,N alpha-dimethylhistamine, N alpha-methylhistamine, 2-pyridylethylamine and 2-thiazolyethylamine produced the largest accumulations of [3H]-inositol-1-phosphate. A very weak response was produced by the H2-selective agonist impromidine, while dimaprit (also H2-selective) was without significant effect. Mepyramine appeared to antagonize competitively the response to the H1-selective agonist 2-pyridylethylamine. This was in contrast to the data obtained with other H1-agonists, where mepyramine produced only a small dextral shift of the agonist curves at low agonist concentrations and an increase in the Hill coefficient. This was particularly striking in the case of 2-methylhistamine. The results suggest that an H1-receptor component in guinea-pig ileum, may coexist with a larger inositol phospholipid response to histamine which is independent of the activation of H1- or H2-receptors.